Decarbonization: Challenges for the electricity market development — Serbian market case - Nebojša Ćorović; Branka Gvozdenac Urošević; Nenad Katić (Energy Reports, 2022)
Decarbonizing the energy sector in order to reduce the consequences of climate change is possible through a comprehensive set of new measures in this sector: integration of a higher share of electricity from renewables and reduction in the share of fossil fuels in the energy mix, improvements in energy efficiency across the board, but also the development of a new, functioning model of the electricity market. As the electricity market is a complex and dynamic environment, this paper highlights that the new vision for the sector outlined here requires a holistic approach with multiple perspectives. The paper focuses on possible challenges in achieving these goals. Having in mind a common vision, it has been up to each country to reshape its domestic energy sector, as well as to use the opportunity to benefit from such a transition to the suggested framework. The contribution of this paper are detailed suggestions for that transition process in the case of the Republic of Serbia. To the best of our knowledge, this is the first paper to systematically explore the evolution of the electricity market design in the Republic of Serbia to ensure a feasible decarbonization process.